2018
DOI: 10.1016/j.meatsci.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Whole cottonseed, vitamin E and finishing period affect the fatty acid profile and sensory traits of meat products from Nellore cattle

Abstract: This study investigated how different finishing periods and the inclusion of whole cottonseed and vitamin E in diets fed to feedlot cattle affect meat lipid composition and sensory traits of fresh beef and hamburgers. Fifty-four Nellore bulls were fed 3 different diets (C: control; WCS: 30% whole cottonseed; WCSE: 30% whole cottonseed plus vitamin E) during finishing periods of 83, 104, and 111days. The inclusion of cottonseed did not affect saturated fatty acid levels (SFA), but increased the levels of certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
1
10
1
Order By: Relevance
“…The sensory analysis revealed that the tasters considered most of the parameters analyzed, with average scores between 5.30 and 6.74 according to the hedonic scale, e.g., most scores were indifferent (5) or like moderately (7) (Table 1). Similar results, with scores ranging from 6.7 to 7.2, were reported by Eiras et al (2017), who analyzed parameters of acceptability of meat from young bulls fed cottonseed hulls; additionally, scores ranging from 6.4 to 7.1 were reported for meat from Nellore bulls that were fed whole cottonseed and whole cottonseed plus vitamin E by Ferrinho et al (2018). In general, these results showed that the score of the sensory traits of beef could not be associated with the specific use of cottonseed in the feed of animals.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The sensory analysis revealed that the tasters considered most of the parameters analyzed, with average scores between 5.30 and 6.74 according to the hedonic scale, e.g., most scores were indifferent (5) or like moderately (7) (Table 1). Similar results, with scores ranging from 6.7 to 7.2, were reported by Eiras et al (2017), who analyzed parameters of acceptability of meat from young bulls fed cottonseed hulls; additionally, scores ranging from 6.4 to 7.1 were reported for meat from Nellore bulls that were fed whole cottonseed and whole cottonseed plus vitamin E by Ferrinho et al (2018). In general, these results showed that the score of the sensory traits of beef could not be associated with the specific use of cottonseed in the feed of animals.…”
Section: Resultssupporting
confidence: 84%
“…The use of this byproduct has increased annually in Brazil, and although some farms have used whole cottonseed in feedlots for fattening cattle, others have avoided the use of this byproduct, fearing the appearance of a "strange flavor, " such as "liver" or other flavors, in beef. To answer this question, several authors have studied beef from cattle fed cottonseed at different levels or compared it to other feeds; however, the authors were not able to determine the influence of using this byproduct on the sensory traits of meat from fattening animals (Costa et al, 2013;Ferrinho et al, 2018;Polizel Neto et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, Ferrinho et al [91] observed differences in FA composition as a function of the cottonseed inclusion level in the diet. The total SFAs were not affected by diet, but differences were observed for branched chain fatty acids (BCFA), cis-and trans-monounsaturated fatty acid (MUFAcis/trans), unconjugated (nc) dienes, and in some individual PUFA.…”
Section: The Influence Of Diet On the Meat Fatty Acid Compositionmentioning
confidence: 99%
“…Cattle fed with grain increases the absolute monounsaturated and saturated fat content of the meat while simultaneously decreasing absolute content of n-3 [89,90]. Accordingly, Ferrinho et al [91] observed differences in FA composition as a function of the cottonseed inclusion level in the diet. The total SFAs were not affected by diet, but differences were observed for branched chain fatty acids (BCFA), cis-and trans-monounsaturated fatty acid (MUFAcis/trans), unconjugated (nc) dienes, and in some individual PUFA.…”
Section: The Influence Of Diet On the Meat Fatty Acid Compositionmentioning
confidence: 98%